Common Fixed Point Theorem For Rational Expressions In 2-Banach Spaces - GOYAL, A.K.; Garg, Gaurav Kumar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The study of non-contraction mapping concerning the existence of fixed points draws attention of various authors in non-linear analysis. Gahlar [6] introduced the concept of 2- Banach spaces. Badshah and Gupta [3] , Yadava, Rajput, Choudhary and Bhardwaj [26] proved some results on fixed point in 2-Banach spaces. Recently Yadava,Rajput, Bhardwaj [25] proved a result on fixed point in 2- Banach spaces for non- contraction mappings. In this paper we prove some common fixed point theorems for non-contraction mappings in 2-Banach spaces, which contains new rational expressions. 2010 AMS Mathematics Subject Classification: 46B20, 46B25